Multicultural education-oriented digital teaching materials to improve students' pluralist attitudes - Uswatun Hasanah; Arita Marini; Arifin Maksum (Jurnal Prima Edukasia, 2021)
This study aims to analyze the effectiveness of digital teaching materials oriented to multicultural education in improving students' pluralist attitudes. The type of research method used is a quantitative method with a quasi-experimental design and a one-group pretest-posttest design with a control group design. The sample used was 108 grade V elementary school students in Setiabudi sub-district who were selected by the probability sampling technique. The results of this study prove that the use of digital teaching materials oriented to multicultural education has a significant value so that it is effectively used in improving students' pluralistic attitudes. This digital teaching material allows students to analyze moral values conveyed through story content. The results of this study can provide contributions and solutions for education practitioners in order to instill multicultural education since elementary school age so as to create a pluralist generation of youth with diversity.